Lygia Pape: Hibridismos e Experimentações Poéticas nas Décadas de 1960 e 1970 - Soares, Erani Ferreira (2022)
This research analyzes art, language and hybridism in the work of the artist Lygia Pape, one of the most important representatives of Neoconcretism in Brazil in the 1960s. Permeing the limit between art and life, Lygia Pape, made their work an interaction with the world. Born in 1929, in Nova Friburgo, a city in the State of Rio de Janeiro, the artist became known internationally for her work. Our aim is to achieve meanings in his works, as hybridization occurs in the process of building his plastic, specifically in the 1960s and 1970s, a period when the political-military regime was severe. The artist was also part of the moment when the feminist movement was strengthened in Brazil, in it, women claimed freedom of sexual, of own body and of expression.